Pengaruh Urban Sprawl terhadap Kondisi Fisik Kota: Studi Kasus Kecamatan Bojongloa Kidul - Wanda Yolanda; Sri Hidayati Djoeffan (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Urban sprawl is an unplanned urban development due to the tendency of residents to live in suburban areas. Bojongloa Kidul District is a sub-district located in a suburban area bordering Bandung Regency, where in 2005 Bojongloa Kidul District was the District with the lowest urban sprawl typology, and in 2018 it became the highest urban sprawl typology. The purpose of this study was to determine the effect of urban sprawl on the physical condition of the city in Bojongloa Kidul District. The method used in this study is a mixed method with quantitative and qualitative analysis techniques. The stages of the analysis method in this study are the analysis of the identification of the sprawl area, the analysis of the characteristics of the sprawl using population density analysis, analysis of building density, analysis of the distance to the center of the CBD, and analysis of development within the reach of the road network, analysis of the ANOVA statistical method. Based on the results of the study, it shows that the urban sprawl indicated urban sprawl in 2011 and 2021 are Cibaduyut, Cibaduyut Kidul, Cibaduyut Wetan, and Mekarwangi villages. The typology of urban sprawl in the Kelurahan indicated for sprawl in 2011 and 2021 is Typology I, Kelurahan Siteaeur and Kelurahan Kebonlega, which from 2011 was in typology II changed to typology I, typology II Cibaduyut and Cibaduyut Kidul Villages and typology III Mekarwangi and Cibaduyut Wetan Villages. There is an influence of urban sprawl typology on the variables of percentage changes in land use, road network patterns and changes in building functions. Abstrak. Urban sprawl merupakan perkembangan kota yang tidak terencana karena kecenderungan penduduk untuk bermukim di area pinggiran kota. Kecamatan Bojongloa Kidul merupakan Kecamatan yang berada di area pinggiran kota berbatasan dengan Kabupaten Bandung, dimana pada tahun 2005 Kecamatan Bojongloa Kidul merupakan Kecamatan dengan tipologi urban sprawl paling rendah, dan pada tahun 2018 menjadi tipologi urban sprawl paling tinggi. Tujuan dalam penelitian ini adalah untuk mengetahui pengaruh urban sprawl terhadap kondisi fisik kota di Kecamatan Bojongloa Kidul. Metode yang digunakan dalam penelitian ini adalah mixed method dengan teknik analisis kuantitatif dan kualitatif. Tahapan metode analisis dalam penelitian ini adalah analisis identifikasi kawasan sprawl, analisis karakteristik sprawl menggunakan analisis kepadatan penduduk, analisis kepadatan bangunan, analisis jarak ke pusat CBD, dan analisis pembangunan dalam jangkauan jaringan jalan, analisis metode statistik ANOVA. Berdasarkan hasil penelitian menunjukkan bahwa Kelurahan yang terindikasi urban sprawl pada tahun 2011 dan 2021 adalah Kelurahan Cibaduyut, Cibaduyut Kidul, Cibaduyut Wetan, dan Mekarwangi. Tipologi urban sprawl di Kelurahan terindikasi sprawl tahun 2011 dan 2021 adalah Tipologi I Kelurahan Situsaeur dan Kelurahan Kebonlega yang dari 2011 berada di tipologi II berubah menjadi tipologi I, tipologi II Kelurahan Cibaduyut dan Cibaduyut Kidul serta tipologi III Kelurahan Mekarwangi dan Cibaduyut Wetan. Terdapat pengaruh tipologi urban sprawl terhadap variabel persentase perubahan tata guna lahan, pola jaringan jalan dan perubahan fungsi bangunan.